2018
DOI: 10.13005/bbra/2638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Coated Urea on in vitro Gas Production of Dairy Cow

Abstract: In this experiment the effects of different urea products (urea, Paraffin-sulfur Coated Urea (PSCU) and controlled release urea product (Optigen, Alltech Inc., Lexington, KY)) on rumen fermentation were investigated in dependence of different diet sources by using in vitro techniques. The experiment followed a completely randomized design using four N-source treatmentes (urea, Paraffin-sulfur Coated Urea, Optigen and canola meal) in four diets (wheat straw+ %3 isonitrogenous of each N-source, barley grain+ %3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Polymer-coated urea (PCU) is one of the newest coated urea products that coated with oil materials. Th is product showed positive effects in slowing rate of urea degradation urea compare with other expensive coated -urea products in previous studies (Mazinani, Naserian, Mesgaran, & Valizadeh, 2018).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Polymer-coated urea (PCU) is one of the newest coated urea products that coated with oil materials. Th is product showed positive effects in slowing rate of urea degradation urea compare with other expensive coated -urea products in previous studies (Mazinani, Naserian, Mesgaran, & Valizadeh, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Cherdthong et al (2011) reported an increase in total milk yield by dairy cows fed urea-calcium. Mazinani et al (2018) reported that supplementing urea can elevate blood urea concentration more than canola meal and it is due to rapid hydrolysis of urea to ammonia in the rumen .excess ammonia is absorbed into the blood from the rumen wall and then taken to the rumen where urea is usually detoxified. part of this urea can recycle by the rumen while the excess amount is excreted in the urine (Lapierre & Lobley, 2001).…”
Section: Microbial Nitrogen Synthesismentioning
confidence: 99%
“…Penghambatan hidrolisis urea dapat dilakukan melalui pencampuran urea dengan gelatin (Paengkoum and Bunnakit, 2012). Melalui gelatinisasi terjadi peningkatan degradabilitas karbohidrat dalam ransum dan alternatif lainnya menurunnya laju degradasi urea (Mazinani et al, 2018).…”
Section: Pendahuluanunclassified
“…Protein, an essential and expensive nutrient in animal diets, especially for high-performance cattle, is often a limiting factor [1]. Ruminants mainly derive their amino acids (AA) from dietary protein that escapes rumen degradation and from microbial proteins [2].…”
Section: Introductionmentioning
confidence: 99%